1998
DOI: 10.1104/pp.117.4.1411
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Glutamate Decarboxylase cDNA Clones from Arabidopsis

Abstract: Two distinct cDNA clones encoding for the glutamate decarboxylase (GAD) isoenzymes GAD1 and GAD2 from Arabidopsis (L.) Heynh. were characterized. The open reading frames for GAD1 and GAD2 were expressed in Escherichia coli and the recombinant proteins were purified by affinity chromatography. Analysis of the recombinant proteins by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and immunoblot analysis suggest that GAD1 and GAD2 encode for 58-and 56-kD peptides, respectively. The enzymatic activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 47 publications
9
68
0
Order By: Relevance
“…However, our results clearly indicate that the predicted inhibition of the GABA shunt activity does not affect the isotope between GABA and succinate. In contrast, the data support the hypothesis that the consumption of protons by Glu decarboxylase for the production of GABA can help to stabilize the cytosolic pH during exposure to different stress conditions, including hypoxia (Turano and Fang, 1998;Shelp et al, 2012).…”
Section: Table I Gc-tof-ms Primary Metabolite Profiling Of Soybean Rsupporting
confidence: 73%
“…However, our results clearly indicate that the predicted inhibition of the GABA shunt activity does not affect the isotope between GABA and succinate. In contrast, the data support the hypothesis that the consumption of protons by Glu decarboxylase for the production of GABA can help to stabilize the cytosolic pH during exposure to different stress conditions, including hypoxia (Turano and Fang, 1998;Shelp et al, 2012).…”
Section: Table I Gc-tof-ms Primary Metabolite Profiling Of Soybean Rsupporting
confidence: 73%
“…5). GABA is formed from glutamate by glutamate decarboxylase (GAD), which is activated by Ca 2+ /CaM (Aurisano et al, 1995;Snedden et al, 1995Snedden et al, , 1996Turano and Fang, 1998) and acidic pH (Johnson et al, 1997;Snedden et al, 1996). Although salinity stress increased the acidity of the fruit, as described above, we could not determine whether it directly enhanced GABA accumulation because it has been reported that the cellular Ca 2+ level generally increases with salinity stress in plant cells (Sanders et al, 1999).…”
Section: Resultsmentioning
confidence: 97%
“…There have also been reports of a crucial role for Ca 2+ and calmodulin in the regulation of GAD activity in many plants (Baum et al, 1996;Snedden et al, 1995;Turano and Fang, 1998). It is possible that an increase in intracellular Ca 2+ caused by salinity stress stimulates GAD activity, resulting in increased fruit GABA levels.…”
Section: Discussionmentioning
confidence: 99%